IMPACT OF GLOBALISATION ON HIGHER EDUCATION IN INDIA: CHALLENGES AND PRESCRIPTIVES (International Journal of Food and Nutritional Sciences, 2022)
Education is the backbone of a nation. So education should be acquired from the cradle to grave. Higher education occupies the apex of educational pyramid in the formal process of education. Generally it compromises of three stages-graduate, post graduate and research programme i.e. M.Phil and Ph.D. Higher education also comprises of general, technical, commercial, medical, engineering, law and other professional degrees and diplomas. Therefore the scope of operation of higher education is extensive and intensive. It is intensive the sense that, it provides a broad prospective of opportunities to the students about almost all the aspect of our life. In the recent year efforts have been made by the commission to regulate the growth of higher education as well as the establishment of new universities and colleges with a view to ensuring that, higher education grows to meet the genuine needs of the society for trained manpower with appropriate level of professional training. Globalisation increases the demand for higher education and for educational quality.